The Role of Calotropis gigantea Leaves as a Natural Binder in Corncob Briquettes Enhanced with LDPE - Zeni Ulma; Syabriyana, Maliya; Livia Ayu Ardilasari (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Briquetting represents one of the key technological pathways for biomass utilization, particularly when combined with plastic waste that is otherwise difficult to manage. This study aims to analyze the effect of Calotropis gigantea (Biduri leaves) as a natural binder on the characteristics of briquettes made from corncob charcoal and low-density polyethylene (LDPE) plastic waste. Corncobs were carbonized at 300-400 °C for approximately 4 hours, and briquettes were formulated with a constant corncob-to-LDPE ratio of 70:30. Five binder compositions (15%, 20%, 25%, 30%, and 35% of total briquette mass) were tested to determine the optimal formulation. Physical and chemical properties including moisture content, ash content, volatile matter, fixed carbon, calorific value, density, and bulk density, were analyzed. The results demonstrated that the 15% binder composition (V1) achieved the best performance, meeting SNI requirements with a moisture content of 2.947%, ash content of 6.790%, volatile matter of 3.536%, fixed carbon of 86.727%, calorific value of 7216.649 cal/g, density of 0.932 g/cm³, and bulk density of 0.326 g/cm³. This research highlights the novelty of employing Calotropis gigantea leaves as a sustainable binder in LDPE-modified biomass briquettes. The findings confirm that natural binders can enhance briquette quality while reducing reliance on synthetic adhesives, offering a viable pathway toward environmentally friendly household energy solutions.